2016
DOI: 10.1103/physrevb.93.094502
|View full text |Cite
|
Sign up to set email alerts
|

Fermi surface reconstruction and quantum oscillations in underdopedYBa2Cu3O7xmodeled in a single bilayer with mirror symmetry broken by charge density waves

Abstract: Hole-doped high-temperature cuprate superconductors below optimum doping have electronlike Fermi surfaces occupying a small fraction of the Brillouin zone. There is strong evidence that this is linked to charge density wave (CDW) order, which reconstructs the large holelike Fermi surfaces predicted by band structure calculations. Recent experiments have revealed the structure of the two CDW components in the benchmark bilayer material YBa 2 Cu 3 O 7-x in high field where quantum oscillation (QO) measurements a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 69 publications
5
33
0
Order By: Relevance
“…This points to a Fermi surface with a square or diamond-like in-plane geometrystrikingly similar to the Fermi surface reconstruction predicted to occur via CDW. 17,[23][24][25][26][27] Two scenarios that could give rise to this type of reconstruction are shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This points to a Fermi surface with a square or diamond-like in-plane geometrystrikingly similar to the Fermi surface reconstruction predicted to occur via CDW. 17,[23][24][25][26][27] Two scenarios that could give rise to this type of reconstruction are shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…We suggest that this asymmetry in the ĉ-axis components of the wavevectors persists to at least 45 T, and that these CDWs are responsible for the Fermi surface reconstruction, as has been proposed theoretically. 17,[23][24][25][26][27] A second route to a diamond-like pocket with C 2 symmetry in the ĉ-axis tunneling requires a strong nematic distortion of the Fermi surface (see Fig. 3d, e).…”
Section: Discussionmentioning
confidence: 99%
“…There have been many proposals [32][33][34][35][36][37][38][39][40][41][42][43] for the origin of the Fermi surface reconstruction in the cuprates. Given recent observations of (seemingly ubiquitous [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] ) incommensurate CDW order, a prime candidate for the Fermi surface is one where nodally located electron pockets are produced by incommensurate CDWs which are at least bi-axial, involving ordering at Q x = (Q, 0, 1/2) and Q y = (0, Q, 1/2).…”
Section: A Comparison With Previous Proposalsmentioning
confidence: 99%
“…Indeed, there is evidence for such broken symmetry in the low field charge order. 31,42 Once mirror symmetry is broken, a natural consequence is that the central 530T frequency reflects a semiclassical orbit where electrons are confined to a single layer of the bilayer, and if so, is naturally the most prominent in the regime of small interlayer tunneling. 72 We have demonstrated that the experimental observations can be generally accounted for in the context of a minimal model of a single bilayer.…”
Section: A Comparison With Previous Proposalsmentioning
confidence: 99%
See 1 more Smart Citation